(untitled) (Colombia Medica, 2009)
Objective: To describe the repair process of inguinal hernias according to the Rutkow and Robbins technique (plug and patch) and polypropylene mesh. Methods: A descriptive study was performed on 102 patients attending to the Surgery Clinic at Hospital Dr. Manuel Noriega Trigo, San Francisco, Venezuela. Patients had a diagnosis of primary inguinal hernia during the period of January 2002 to September, 2005. 124 hernioplasties were practiced, 11 patients received surgery for bilateral hernias. Variables in this study included: sex, age, hernia type, surgical time, postoperation pain, period of hospital staying, time for returning to daily activities, and complications. Results: Ninety one males (89.2%) and eleven females (10.8%) were included in this study. Average age was of 42.7±18.29 years (Range, 12-82) and the more frequent age group lies between 21 to 30 years (23.5%). Inguinal indirect hernia was more common on males (n=47, 25.5% right side. 20.6% left side). The direct inguinal hernia was present on 4 females (3.9%). The duration of the surgical procedure was 32.18±6.42 minutes. Postoperative pain was reported as discomfort (33.3%), mild (39.2%), moderate (8.8%), and no patients reported severe pain. Duration of hospital stay was 23.41±3.8 hours (Range, 3 to 40 hours), time for returning to daily activities was 21.56±6.5 days (Range, 10 to 40). The postoperative complications presented on 6.9% of the patients: 1% wound infection, 1% hematoma, 2% seromas, 1% inguinal neuralgia and 2% urinary retention. Conclusion: This is a quick technique associated with little postoperative morbidity, short hospital stay, short time for returning to daily activities and rare complications. This technique proves to be safe for the repair of inguinal hernias.